ANALYSIS OF MARKETING STRATEGY OF BRAND NONMIN DRINKING WATER OF OXYGEN IN PT TAMANBALI TIRTA BANGLI - Kartika, I Made; Wahyudi, Kadek; Suwandana, I Made Adi; Suteja, Ida Bagus (ADI Journal on Recent Innovation, 2020)
This study raised the title an analysis of marketing strategy of brand NonMin drinking water of oxygen in PT TamanbaliTirtaBangli. As for that being the formulation of research problem is whether that be strengths, weaknesses, opportunities and threats faced by PT. TirtaTamanbaliBangli in an effort to increase the value of sales and how does the marketing mix strategies to increase the value of relevant sales brand oxygen NonMin drinking water on PT TamanbaliTirtaBangli.The results showed that the identification and analysis of the internal factors on the strength variable had the greatest value is the completeness of Nonmin drinking water facilities as well as a source of funding that is adequate for the company's operations, which demonstrated with a score of 0.46 respectively, while in variable weakness that has the greatest value is less intense sales promotion activities with a score that is 0.42.